2020
DOI: 10.1002/jso.26147
|View full text |Cite
|
Sign up to set email alerts
|

Improved oncologic outcomes for minimally invasive left pancreatectomy: Propensity‐score matched analysis of the National Cancer Database

Abstract: Background and objectives: Minimally invasive (MIS) left pancreatectomy (LP) is increasingly used to treat pancreatic adenocarcinoma (PDAC). Despite improved short-term outcomes, no studies have demonstrated long-term benefits over open resection. Methods: The National Cancer Database was queried between 2010 and 2016 for patients with PDAC, grouped by surgical approach (MIS vs open). Demographics, comorbidities, clinical staging, and pathologic staging were used for propensity-score matching. Perioperative, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Qu et al38 analyzed only cases of PDAC with PSM and showed significantly lower conversion rates in RDP than in LDP (5.7% and 22.9%, P = .04). Watson et al49 analyzed the NCDB and showed the same results (15.2% in RDP vs 24.4% in LDP, P = .016). Thus, RDP is favorable in terms of lower rates of conversion to laparotomy and comparable postoperative outcomes.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Qu et al38 analyzed only cases of PDAC with PSM and showed significantly lower conversion rates in RDP than in LDP (5.7% and 22.9%, P = .04). Watson et al49 analyzed the NCDB and showed the same results (15.2% in RDP vs 24.4% in LDP, P = .016). Thus, RDP is favorable in terms of lower rates of conversion to laparotomy and comparable postoperative outcomes.…”
mentioning
confidence: 72%
“…In one of these three reports, Liu et al34 reported that the conversion rates were significantly lower in association with RDP than with LDP (2.9% and 9.8%, P = .045), while De et al40 showed no significant difference.Qu et al38 analyzed only cases of PDAC with PSM and showed significantly lower conversion rates in RDP than in LDP (5.7% and 22.9%, P = .04). Watson et al49 analyzed the NCDB and showed the same results (15.2% in RDP vs 24.4% in LDP, P = .016).…”
mentioning
confidence: 72%
“…RPS is one of the latest advances in minimally invasive surgery and receives a lot of attention [6]. Mainly for distal pancreatectomies published results of RPS seem promising, also with respect to the oncological outcomes [5]. Moreover, The International Study Group on Minimally Invasive Pancreatic Surgery documented that minimally invasive distal pancreatectomy may be superior to open surgery in selected cases [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, benign or low-grade malignant tumors of the pancreatic tail are mainly addressed by minimally invasive distal pancreatectomy [3]. Furthermore, Watson et al demonstrated an improved oncological outcome in patients undergoing minimally invasive procedures for malignant indications [5].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies using NCDB by Raoof et al [34] and Watson et al [31] found that RDP had a lower conversion rate than LDP but no statistical differences in hospital stay and 90-day mortality for PDAC. The single-center retrospective study reported that RDP might have longer operative time than LDP but no statistical differences in intraoperative blood loss and postoperative pancreatic fistula for PDAC.…”
Section: Introductionmentioning
confidence: 99%